2021
DOI: 10.3390/en14196110
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information and Communication Technologies (ICT) on Energy Poverty and Unemployment in Selected European Union Countries

Abstract: The accelerated development of information and communication technologies (ICT) over the last three decades has encouraged researchers to analyse the impact of this phenomenon on the labour market. The potential decline in employment resulting from the proliferation of ICT may reduce access to basic energy services and even lead to energy poverty in the form of inability to heat the apartment as needed, allocating a significant part of revenues to expenses related to heating or problems with the timely payment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The results of the study [13] show that increasing internet use has a multidimensional impact on poverty reduction in rural China. The same thing was also found by Yilmaz and Koyuncu [14]; Zhang [15]; Pradhan [12], ICT penetration can lead to higher economic growth; the results showed that increasing access to information had a significant positive effect on poverty reduction efforts [16]. Research in Bangladesh shows that ICT has a very good ability to alleviate poverty despite the many challenges that must be faced [17].…”
Section: Introductionsupporting
confidence: 59%
“…The results of the study [13] show that increasing internet use has a multidimensional impact on poverty reduction in rural China. The same thing was also found by Yilmaz and Koyuncu [14]; Zhang [15]; Pradhan [12], ICT penetration can lead to higher economic growth; the results showed that increasing access to information had a significant positive effect on poverty reduction efforts [16]. Research in Bangladesh shows that ICT has a very good ability to alleviate poverty despite the many challenges that must be faced [17].…”
Section: Introductionsupporting
confidence: 59%
“…Furthermore, the deployment of ICT services is expected to generate more or fewer employment opportunities and, hence, have an ambiguous effect on the poverty rate (Metu et al, 2021; Nipo et al, 2019; Postuła et al, 2021). Within the broad spectrum of ICT‐enabled employment, there are two specific intersections.…”
Section: Literature Review and Contextual Backgroundmentioning
confidence: 99%
“…The proliferation of ICTs might also negatively affect employability (increase the unemployment rate, Brouwer et al, 1993; Machin & Van Reenen, 1998). Since ICT might affect the labor market (employment) negatively or positively, empirical studies on the influence of ICT infrastructure on employability have not been robust (Metu et al, 2021; Nipo et al, 2019; Postuła et al, 2021). This situation is because such an impact depends on other factors, such as; the skills of the labor force, the age structure of the labor force, affordability of ICT services, and the economy's structure (Metu et al, 2021).…”
Section: Literature Review and Contextual Backgroundmentioning
confidence: 99%